2021
DOI: 10.3389/fphar.2021.642511
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Conversion Surgery Following Apatinib Plus Paclitaxel/S1 for Advanced Gastric Cancer With Unresectable Factors: A Multicenter, Single-Arm, Phase II Trial

Abstract: Objective: Conversion therapy (surgical resection after chemotherapy) is a promising option for unresectable gastric cancer (GC) patients. Addition of anti-angiogenesis drug improves response to chemotherapy. Hence, this study explored the feasibility and efficacy of preoperative paclitaxel (PTX)/S1 chemotherapy combined with apatinib for unresectable GC.Methods: Thirty-one eligible patients with a single unresectable factor were enrolled in this multi-center, single-arm trial. Apatinib (500 mg qd) was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The reason might lie in that apatinib is a small molecular tyrosine kinase, which has a much shorter half-life (about 9 h) than antibodies (e.g., about 20 days for bevacizumab) 40,41 . Consistent with this, adding apatinib to conversion chemotherapy showed no anastomotic leakage or wound-healing complications in patients with advanced gastric cancer 42 . By comparing baseline pathology and omics data between patients with different responses, we identified potential biomarkers associated with pathological responses.…”
Section: Discussionsupporting
confidence: 71%
“…The reason might lie in that apatinib is a small molecular tyrosine kinase, which has a much shorter half-life (about 9 h) than antibodies (e.g., about 20 days for bevacizumab) 40,41 . Consistent with this, adding apatinib to conversion chemotherapy showed no anastomotic leakage or wound-healing complications in patients with advanced gastric cancer 42 . By comparing baseline pathology and omics data between patients with different responses, we identified potential biomarkers associated with pathological responses.…”
Section: Discussionsupporting
confidence: 71%
“…[16,19,24,28,31] Few investigators have studied the role of speci c chemotherapy regimens, but there is no head to head comparison of different regimens. [22,32,33] The present study showed a signi cant survival advantage of EOX and DOX regimen over FLOT, but this could be biased due to the small sample size. Institutional guidelines may be followed in deciding the optimal chemotherapy regimen for conversion therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Antiangiogenic therapy was associated with potentially serious toxic effects, such as gastrointestinal perforation, hemorrhage, and delayed wound-healing, presenting additional challenges to neoadjuvant chemotherapy. Previous clinical trials had shown that patients with several solid tumors receive apatinib at dose of 500-850 mg/day [ 20 ]. Considering the toxicity of TP, we used 425 mg/day as the initial dose of apatinib in this study.…”
Section: Discussionmentioning
confidence: 99%